The Influence of the Sun's Position to Changes In Rainfall Patterns in Banda Aceh and Aceh Besar - Hulul Fitri; Suhrawardi Ilyas; Fadhli . (PSI-Aceh, 2014)
People often perceived that weather pattern is irreguler and unpredictable. Therefore it is necessary to investigate the relationship between position of the sun above earth's surface and the change on rainfall patterns in the region of Banda Aceh and surrounding. Aceh region is located at the tip of Sumatra island and at the perimeter of three major oceans. This location greatly affect rainfall patterns in Banda Aceh and Aceh Besar. The aims of this research are to determine the variation in weather pattern, especially rainfall and to draw up a general pattern of weather oscillation, especially rainfall in the region of Banda Aceh and Aceh Besar. The position of sun relative to Banda Aceh was then visually sketched on a world map. The map is used to analyze relations between rain frequency, duration and time with sun’s position over land and sea, based on the rain pattern condition in six months from Desember 2013 until Mei 2014. The result showed that from Desember until February, rain mostly occured at night and water vapor came from Indian Ocean. Meanwhile in March and May, rain are more common in the morning when the sun’s position was above Indian Ocean and Sea of Bengal. However in April rainfall occur during the day, because of evaporation was brought from the South China Sea.